Ectopic BAT mUCP-1 overexpression in SKM by delivering a BMP7/PRDM16/PGC-1a gene cocktail or single PRMD16 using non-viral UTMD gene therapy. Issue 7 (October 2018) - Chen, Shuyuan; Bastarrachea, Raul; Shen, Jin-Song; Laviada-Nagel, Antonio; Rodriguez-Ayala, Ernesto; Nava-Gonzalez, Edna; Huang, Pintong; DeFronzo, Ralph; Kent, Jack; Grayburn, Paul
Abstract Here we present our progress in inducing an ectopic brown adipose tissue (BAT) phenotype in skeletal muscle (SKM) as a potential gene therapy for obesity and its comorbidities. We used ultrasound-targeted microbubble destruction (UTMD), a novel targeted, non-viral approach to gene therapy, to deliver genes in the BAT differentiation pathway into rodent SKM to engineer a thermogenic BAT phenotype with ectopicmUCP-1 overexpression. In parallel, we performed a second protocol using wild-typeUcp-1 -null knockout mice to test whether the effects of the gene therapy are UCP-1 dependent. Our main findings were a robust cellular presence ofmUCP-1 immunostaining (IHC), significantly higher expression levels ofmUCP-1 measured by qRT-PCR, and highest temperature elevation measured by infrared thermography in the treated thigh, achieved in rats after delivering the UTMD-PRDM16/PGC-1a/BMP7 /hyPB gene cocktail. Interestingly, the weight loss obtained in the treated rats with the triple gene delivery, never recovered the levels observed in the controls in spite of food intake recovery. Our results establish the feasibility of minimally invasive UTMD gene-based therapy administration in SKM, to induce overexpression of ectopicmUCP-1 after delivery of the thermogenic BAT gene program, and describe systemic effects of this intervention on food intake, weight loss, and thermogenesis.